In vitro effect of platelet-rich plasma (PRP) on morpho-functional characteristics, oxidative stress, apoptosis and CatSper-1 ion channel in short-term stored (5 °C) ram semen - Turk, Gaffari; Gungor, Ibrahim brahim Halil; Arkali, Gozde; Cihangiroglu, Aslihan Cakir; Badilli, Nida; Acisu, Tutku Can; Yuce, Abdurrauf (Elsevier, 2025)
The objective of this study was to examine the impact of platelet-rich plasma (PRP) on the morpho-functional characteristics, oxidative stress, apoptosis and CatSper-1 ion channel in short-term stored ram semen at 5 degrees C. The study was conducted in six independent replicates on pooled semen samples collected by artificial vagina from six sexually active Akkaraman rams. The pooled semen samples were diluted to a concentration of 400 million spermatozoa per milliliter with a tris-based diluent including 6 PRP concentration (1, 2, 4, 8, 10, 20 %) and no PRP (control) at 38 degrees C. Following the reduction of the temperature to 5 degrees C, diluted semen samples were stored for a period of 96 hours. Motility (total, progressive, rapid, medium, low), kinematic (VCL, VSL, VAP, LIN, STR, WOB, ALH, BCF), morphological (plasma membrane integrity, abnormality), flow-cytometric (mitochondrial activity, acrosomal damage, viability, apoptosis), oxidative stress (MDA, GSH, GSH-Px, CAT), and CatSper-1 analyses were performed at both hours zero (initial measurement) and 96. In all groups, a time-dependent deterioration was observed in nearly all parameters at 96 h in comparison to the 0 h. Compared to the control, live spermatozoon rates (8 % and 10 %), GSH-Px (4 %, 8 % and 10 %) and CAT (4 % and 8 %) activities, and CatSper-1 levels at 96 h were higher, while the apoptotic spermatozoon rates (8 % and 10 %) and MDA levels (4 %, 8 % and 10 %) were lower in semen samples containing PRP. However, in semen samples containing 20 % PRP, the apoptotic spermatozoon rates and MDA levels at 96 h were higher, while GSH-Px activity and CatSper-1 levels were lower than in the control. As a result, it was concluded that the addition of 4-10 % PRP to the diluent containing tris+egg yolk has an effective role in preventing oxidative, apoptotic and ion channel (CatSper-1) damages in ram spermatozoa stored for a short time at 5 degrees C, while the concentration of 20 % is harmful.
Keywords: Platelet-rich plasma; Semen; Apoptosis; CatSper-1; Oxidative stress; Ram